Hydrolysis of 4-Fluoroaniline Phosphate Monoester in Acid Solutions - Kushwaha, R.S.; Sharma, Renu (Asian Journal of Chemistry, 2010)
Hydrolysis of 4-fluoroaniline phosphate monoester has been carried out in HCl solution at 97 ± 0.5ºC and the inorganic phosphate obtained during hydrolysis has been estimated colorimetrically. Pseudo first order rate coefficients have been calculated. Conjugate acid species along with neutral species have been found to be reactive and contribute to overall hydrolysis in the acid region. The calculated rate coefficients are in good agreement with the experimentally observed ones. The effects of temperature, solvent and [substrate] on the rate have been studied. The results suggest that the hydrolysis of monoester occurs by cleavage of P-N bond.